The Mechanism of Calcitonin Gene-Related Peptide-Containing Nerve Innervation - Narumi Hashikawa-Hobara; Naoya Hashikawa; Yoshito Zamami; Shingo Takatori; Hiromu Kawasaki (Elsevier, 2012)
Calcitonin gene-related peptide (CGRP) is a major neurotransmitter and CGRP-containing primary sensory neurons play an important role in nociception and potent vasodilation. CGRP-containing nerves in mesenteric arteries are decreased in pathological animal models (hypertension, diabetes, and atherosclerosis). In apolipoprotein E-knockout mice, which have atherosclerosis and peripheral sensory nerve defects, nerve growth factor (NGF)-mediated CGRP nerve facilitation was down-regulated, which may have been caused by the impairment of the Akt-NO-cGMP pathway. In addition, NGF-mediated CGRP neurite outgrowth was decreased in fructose-induced insulin-resistant rats. We recently discovered that renin-angiotensin inhibitors improved CGRP innervation in spontaneously hypertensive rats, indicating that rescuing CGRP nerve innervation might improve pathophysiological conditions. To find a novel reagent that facilitates CGRP nerves, a new model, phenol-injured perivascular nerve model rats, was established. Adrenomedullin, hepatocyte growth factor, and angiotensin II type 2 receptor activation induced CGRP nerve distribution in phenol-injured rats. Furthermore, in insulin-resistant model rats, the down-regulation of CGRP nerves was likely due to the depression of phosphoinositide 3-kinase (PI3K)-dependent Akt activation. Administration of candesartan improves CGRPergic function via the PI3K-Akt pathway in insulin-resistant rats. Thus, clarification of the mechanisms of CGRP nerve defects may constitute future therapeutic targets. Keywords:: calcitonin gene-related peptide-containing nerve, nerve growth factor-mediated neurite outgrowth, angiotensin II type 2 receptor, PI3K-Akt pathway